Avaliação da tensão e do deslocamento inicial no ligamento periodontal, de modelos com perda de suporte ósseo alveolar quando submetidos a uma força ortodôntica, por meio do método de elementos finitos - Arashiro, Cassiano (2014)
The aim of this study was to determine the stress and initial displacement in the periodontal ligament when a force of 1N (98g / f) was applied at the center of the crown, at the buccal-lingual direction of a maxillary central incisor using the finite elements method. The stress analysis was evaluated in three models: Model 1 - normal level of alveolar bone crest, Model 2 - 2mm of crestal bone loss and Model 3 - 4mm of crestal bone loss. Special attention was given to areas of tension and compression using maximum and minimum tension test in order to calculate the stresses in these areas. After application of force in buccal-lingual direction, all models had increased concentration of forces in the periodontal ligament and a radual increase in tensions as the bone crest was being reduced. The results of this study indicate that reducing alveolar crest height can contribute to a greater concentration of forces in the periodontal ligament which can possibly induce root resorption, therefore represents an important factor in orthodontic treatment planning in periodontally compromised patients.